Antioxidant effect of zinc picolinate in patients with chronic obstructive pulmonary disease - Kirkil, Gamze; Muz, Mehmet Hamdi; Seckin, Dilara; Şahin, Kazım; Küçük, Ömer (W B Saunders Co Ltd, 2008)
An imbalance between oxidative stress and antioxidant capacity is thought to play an important role in the pathogenesis of chronic obstructive pulmonary disease (COPD). However, studies in regard to stable COPD patients and effect of zinc supplementation are lacking. We investigated the effects of zinc picolinate supplementation on the oxidant stress, and pulmonary function tests (PFTs) of patients with stable COPD. Thirty patients with COPD, and 15 healthy non-smokers who were matched for age and sex were included in the study. Their baseline spirometry, plasma malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), and zinc levels were measured. All parameters were repeated after 8 weeks of supplementation with 22 mg of zinc picolinate daily. The mean MDA levels in the COPD group at baseline were higher than controls (0.51 +/- 0.15 vs 0.39 +/- 0.15 nmol/mL, p = 0.037), while SOD (0.16 +/- 0.022 vs 0.20 +/- 0.04 U/mL, p = 0.000), CAT (14.79 +/- 3.03 vs 17.37 +/- 2.60 k/mL, p=0.008) and zinc levels (77.33 +/- 4.29 vs 91.45 +/- 3.95 mg/dL, p = 0.000) were lower in the patients compared to controls. Eight weeks of zinc supplementation produced significant increase in mean SOD (p = 0.029) and zinc levels (p<0.001). However, no significant change in mean MDA, CAT levels and forced expiratory volume in one second (FEV1) (% predicted), and FEV1/FVC (%) parameters was observed after zinc supplementation. The Pearson's coefficients of correlation between MDA, SOD, CAT, Zn levels and spirometric measurements were not significant on either day 1 nor 8 weeks of zinc supplementation. In conclusion, the results indicate that zinc supplementation may have favorable effects on oxidant-antioxidant balance in patients with COPD. The lack of an effect on PFT may be due to the short duration of the supplementation. Longer duration of zinc supplementation may be necessary to see clinical benefit. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: COPD; antioxidant therapy; pulmonary function tests